2016
DOI: 10.1160/th16-01-0003
|View full text |Cite
|
Sign up to set email alerts
|

External validation of the IMPROVE Bleeding Risk Assessment Model in medical patients

Abstract: The IMPROVE Bleed Risk Assessment Model (RAM) remains the only bleed RAM in hospitalised medical patients using 11 clinical and laboratory factors. The aim of our study was to externally validate the IMPROVE Bleed RAM. A retrospective chart review was conducted between October 1, 2012 and July 31, 2014. We applied the point scoring system to compute risk scores for each patient in the validation sample. We then dichotomised the patients into those with a score <7 (low risk) vs ≥ 7 (high risk), as outlined in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 15 publications
1
62
1
Order By: Relevance
“…A number of prognostic scores have been developed with variable grades of complexity and reproducibility. [7][8][9][10] Unfortunately however, none of the evaluated bleeding scores has an adequate accuracy and power to accurately identify VTE patients at increased risk of major bleeding.…”
Section: The Risk Of Bleeding During Anticoagulationmentioning
confidence: 99%
“…A number of prognostic scores have been developed with variable grades of complexity and reproducibility. [7][8][9][10] Unfortunately however, none of the evaluated bleeding scores has an adequate accuracy and power to accurately identify VTE patients at increased risk of major bleeding.…”
Section: The Risk Of Bleeding During Anticoagulationmentioning
confidence: 99%
“…This is in keeping with the original IMPROVE Bleed RAM derivation cohort, which stratified 9.7% patients as high bleed risk, and with a similar analysis of adult medical patients that used the same RAM . Other external validation studies of the Bleed RAM demonstrated a higher percentage of patients at high bleed risk (19%‐20.7%) …”
Section: Discussionmentioning
confidence: 98%
“…For the assessment of bleed risk, the IMPROVE Bleed RAM remains the only evidence‐derived RAM known to the authors. This tool was derived from the same population as its VTE counterpart, consists of 13 weighted risk factors, and has been validated in two external populations …”
Section: Introductionmentioning
confidence: 99%
“…This difference might be explained by the limited availability of evidence for bleeding risk assessment, resulting in different approaches within each guideline development group. Only recently the IMPROVE bleeding RAM was externally validated [33]. Approximately 20% of the patients were classified with high bleeding risk.…”
Section: Risk Assessment Comparisonmentioning
confidence: 99%